Reconstitution of the field of accounting regulation in Brazil during the adoption of the IFRS - Homero Junior, Paulo Frederico (2018)
In 2010, Brazil completed the convergence towards the International Financial Reporting Standards (IFRS). As the politics of this process has been little explored, the objective of this thesis is to investigate how the field of accounting regulation was reconstituted during the convergence. Relying on the Bourdieusian concepts of field, capital and habitus, the analysis of accounting regulation in Brazil is split into two phases: firstly, the field as of the early-2000s is mapped through a literature review that identifies its main institutional agents. From the early-2000s on, when the discussions about the creation of a private standard-setter began, the linguistic habitus associated to the field is mapped through discursive analyses of several archival data, including parliamentary proceedings and documents issued by institutional agents that operate in the field. This investigation indicates that the constitution of the field was driven by a relationship of accommodation between the State and the accountancy profession. During the 1970s, an interpretative community linked to the capital markets was consolidated, including financial sector regulators and segments of the professional and academic fields, that issued and disseminated Anglo-American inspired accounting standards framed by a decision-usefulness approach. In opposition, during the 1980s the Federal Council of Accounting (Conselho Federal de Contabilidade - CFC) started to dispute the primacy within the field, issuing accounting standards framed by a discourse of scientificity that preserved the Continental-European influence on Brazilian accounting. From the early-2000s on, the efforts to approve the legislative reforms necessary for the adoption of the IFRS were characterised by a high level of discursive homogeneity: it was claimed that such an adoption would enhance the transparency, comprehensibility, comparability and reliability of the financial reports of Brazilian firms, attracting foreign investments and promoting the economic development of the country. However, none of these claims was supported by substantive empirical evidences. Initially, the CFC opposed the creation of a private standard-setter, claiming that it would undermine the self-regulation of the accountancy profession. In October 2005, though, the CFC itself created the Committee of Accounting Pronouncements (Comitê de Pronunciamentos Contábeis - CPC), apparently solving the conflict that had structured the field until then. The influence of taxation on Brazilian accounting practices played a pivotal role in this process, as a common adversary that justified the alliance between the CFC and the capital market pole. As the CPC frames itself as only a translator and interpreter of the IFRS, the field as a whole is not a space of power anymore, given that substantive decisions in the standard-setting process are not made in Brazil. Nevertheless, some regulators still challenge CPC\'s hegemony, requiring firms under their jurisdictions to prepare and disclose alternative sets of accounts. Contributing for a deeper understanding about the role of local agents in the adoption of the IFRS, this thesis suggests that in Brazil this process was conducted by an interpretative community constituted some decades ago, whose agents exchanged the symbolic capital they previously possessed for the economic capital they earned through the expansion of the market for accounting services.